Analytical calculation of the tooth surface contact stress of spur gear pairs with misalignment errors in multiple degrees of freedom. (July 2020) - Wen, Qi; Du, Qungui; Zhai, Xiaochen
Highlights: A method for calculating the contact stress of gears with misalignment errors. The method is effectively verified by the finite element method. Misalignment errors will affect the magnitude and distribution of contact stress. The influence of misalignment errors on contact stress is non-linear. Abstract: Misalignment errors (MEs) in multiple degrees of freedom (multi-DOFs) along gear pair axis are unavoidable under actual working conditions. These MEs lead to changes in tooth surface contact stress (TSCS) and make its accurate calculation complicated and difficult. Unlike the traditional methods of obtaining TSCS with MEs in multi-DOFs via experimental tests, finite element methods (FEMs) or coefficient methods following international standards, a new analytical calculation model is proposed in this paper. The profile equation of a gear pair with MEs in multi-DOFs is first established. Then, a new profile equation for meshing pairs of gear and pinion slices with non-standard shapes that are coplanar with the line of action of the meshing force is obtained. On this basis, the correctness of meshing force transmission, as well as the accuracy and speed of calculation, can be guaranteed with the contact analysis of gear pairs. Finally, the magnitude and distribution of the TSCS of a gear pair with MEs in multi-DOFs are obtained. Compared with the results of a FEM model, the new model can accurately and rapidly calculate the TSCS of a gear pair with MEs in multi-DOFs.